Rare earth elements in the upland soils of northern China: Spatial variation, relationships, and risk assessment. (November 2022) - Lian, Zhongmin; Han, Yixuan; Zhao, Xumao; Xue, Yinglan; Gu, Xiang
Abstract: While global demand for rare earth elements (REEs) is rapidly growing, recent studies have suggested that REEs are pollutants of emerging concern. In this study, the spatial distribution and risk assessments of REEs in the upland soils of northern China were comprehensively investigated. The total REE concentrations ranged from 81 to 180 mg/kg, with average concentrations of 123, 128, and 98.3 mg/kg in the northwestern, northern, and northeastern zones, respectively. The decreasing trend of REE contents from northwest to northeast might be influenced by variation in the REE metallogenic belt distribution, mining activities, and precipitation intensity in these regions. The ratio of light rare elements (LREEs) to heavy rare elements (HREEs) ranged from 5.04 to 9.06, revealing obvious fractionation between them in upland soils and indicating that LREEs enrichment was common in northern China. The significantly positive correlations between the REEs indicated that REEs might frequently coexist and share similar sources in the upland soils of northern China. Based on a modified ecological risk index ( eRI ), REEs were estimated to pose relatively low ecological risks to current environmental residues, with eRI values ranging from 0.564 to 0.984. Fortunately, the estimated daily intakes of REEs from soils for children (1.08–2.41 μg/kg/day) and adults (0.119–0.312 μg/kg/day) were well below the safety thresholds. However, the health risks posed by REEs in upland soils were estimated to be higher for children. Thus, the continuous monitoring of REE abundance in soils is essential to avoid potential health risks. Graphical abstract: Image 1 Highlights: Fourteen REEs in upland soils from northern China were investigated. Spatial distribution of REE contents showed a decreasing trend from west to east. Obvious fractionation between LREEs and HREEs was observed. A modified index demonstrated low ecological risks of REEs in upland soils. REEs in upland soils caused relatively low health risks for local residents.